Transformation of sequential Fortran programs for their parallelization into hybrid clusters in the SAPFOR - Kolganov, Alexander S.; Gusev, Grigory D. (Numerical Methods and Programming (Vychislitel’nye Metody i Programmirovanie), 2022)
The process of parallelizing programs can be difficult due to their optimization for sequential execution. Because of this, the resulting parallel version may be inefficient, and in some cases parallelization is not possible. Transformations of the source code of programs help to solve these problems. This article discusses the implementation of transformations of sequential Fortran programs in the SAPFOR (System FOR Automated Parallelization) system, which make it possible to facilitate the user’s work in the system and significantly reduce the complexity of program parallelization. The application of the implemented transformations in the SAPFOR system is demonstrated on a program that solves a system of non-linear partial differential equations. The performance of the obtained parallel version was also compared with the versions parallelized manually using DVM and MPI technologies.